Implementation of Energy-Saving Lamp With Automatic System Using LDR SENSOR (Light Dependent Resistor) Combination at Village Guard Posts and Mosques in Probolinggo - Rahmansyah, Ahmad Iskandar; Masluha, Siti; Haris, Abd; Mauliddiansari, Ayu Tista (IMPOWERMENT SOCIETY, 2023)
This study presents the design of an energy-saving lamp with an automatic system using LDR (Light Dependent Resistor) sensors. The LDR sensor acts as a light regulator based on its resistance value, influenced by the received light intensity. The sensor activates when there is a slight increase in the received light. This sensor is used in combination with lamps to enable automatic operation, relying on sunlight as an essential aspect. The sensor-controlled lamps remain off during the day and turn on automatically at night due to reduced sunlight. The installation of these sensor-based lamps is implemented in guard posts within residential areas and mushollah to significantly contribute to efficient illumination in the surrounding areas. The benefits of these sensor-based lamps alleviate the need for manual activation by the guards as the lamps function automatically with the integrated sensor system.